A simple pedotransfer function to estimate fine fraction organic carbon contents of surface horizons in French soils - Eva Rabot; Pierre Barré; Claire Chenu; Amicie A. Delahaie; Manuel P. Martin; José-Luis Munera-Echeverri; Nicolas P.A. Saby (Geoderma)
It has been proposed to separate soil organic carbon (SOC) into two physical fractions, i.e., fine fraction organic carbon (OCfine) and coarse fraction organic carbon, to improve our ability to understand controlling factors and predict SOC contents and SOC stability. In this study, we aimed at building a simple pedotransfer function to estimate OCfine content measured using a size fractionation protocol in French soils. We define OCfine as SOC content measured in the < 50 µm fraction. We used information from the French Soil Quality Monitoring Network (RMQS, 706 observations) and from a literature search (245 observations) to build and validate the pedotransfer function. We used the Random Forest algorithm and partial dependence plots in an exploratory data analysis, to analyze the variables influencing OCfine contents and to study the shape of their relationship with OCfine. Using the knowledge gained from the exploratory analysis, we constructed a simple pedotransfer function. A slight inflection in the OCfine content was detected with increasing SOC content and a good approximation of OCfine content was reached using a second-degree polynomial relationship, with distinct coefficients depending on the land cover (i.e., croplands and permanent crops, grasslands, natural grasslands, and forests and shrubs). A cross-validation of the pedotransfer function led to an RMSE of 2.2 g kg−1 and an independent validation led to an RMSE of 2.0 g kg−1. The domain of applicability of the pedotransfer function was defined as being restricted to topsoil horizons and a SOC content ≤ 90 g kg−1. The estimated OCfine is deemed equivalent to a measure after a complete soil dispersion and a size fractionation protocol. The proposed pedotransfer function could be easily used in future soil carbon modeling frameworks. From a land management perspective, the shape of the relationship found between SOC and OCfine encourages increasing SOC levels to store more carbon in soil, including in the OCfine fraction.